Mistisisme dalam Perspektif Filsafat Analitik: Antara Wittgenstein dan Mehdi Ha'iri Yazdi - M. Hidayatullah S. (Jurnal Filsafat "WISDOM", 2004)
Language is a principal instrument for philosopher and as a medium for analysis and reflection. Wittgenstein said, that the order analytical philosophy is to clean away the epistemology from the "good" terms but unclear in it interpretation. Every thing that can be thinks must be able spoken. The limits of my language mean the limits of my world. From this perspective mysticism and mystics experience is nin-sense, because nothing factual reference. From this case, the goal of this study is to find out the epistemology in mysticism and mystic experience. In the study we include the knowledge by presence (ilm al-hudhuri) Ha 'iri as an approach. Ha 'iri said that there is a other knowledge which that can be explanations in limits of language and picture theory. This is knowledge by peresence, which by Wittgenstein aware as some thing which having difference language games from knowledge by correspondece.